HUBUNGAN INTERAKSI TEMAN SEBAYA DENGAN PERILAKU S0SIAL PADA ANAK USIA 5-6 TAHUN DI TK TERPADU TAHFIDZ AISYAH KECAMATAN TALANG KELAPA KABUPATEN BANYUASIN - Nabila, Sulastri; Leny Marlina; Nyimas Atika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study, entitled "The Relationship between Peer Interaction and Social Behavior in 5-6 Year Old Children at TAHFIDZ AISYAH INTEGRATED TK, Talang Kelapa District, Banyuasin Regency," uses a quantitative approach with a correlational approach. The sample size was 30 children, consisting of 15 boys and 15 girls. Data collection techniques used included direct observation at the school, questionnaires, and documentation. The data were then analyzed using reliability, normality, linearity, and hypothesis testing. The results showed a correlation coefficient between variables X and Y. The processed output showed a significance value of 0.634. Therefore, it can be said that the relationship between the two variables is significant or unidirectional, meaning there is a significant relationship between peer interaction and the social behavior of 5-6-year-old children at the Tahfidz Aisyah Integrated Kindergarten in Talang Kelapa District, Banyuasin Regency.